Lust und Leere : Japanische Photographie der Gegenwart. - Matt, Gerald; Weiermair, Peter; Kunsthalle Wien (Kilchberg/Zurich : Edition Stemmle, 1997)
Araki, Nobuyoshi ; Hatakeyama, Naoya ; Hirakawa, Noritoshi ; Ishiuchi, Miyako ; Kanemura, Osamu ; Mori, Mariko ; Morimura, Yasumasa ; Nomura, Sakiko ; Sugimoto Hiroshi ; Yamanaka, Manabu ; Yanagi Miwa ; Yashiro, Toshihiro
biografie, bibliografie
Lust und Leere : Japanische Photographie der Gegenwart, Kunsthalle Wien im Museumsquartier, 25. April bis 20. Juli 1997
Duits
kunstcatalogus
Keywords: Japan